2016
DOI: 10.3329/bjp.v11i1.25487
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization and mode of action of <i>Ligustrum lucidum</i> flower essential oil against food-borne pathogenic bacteria

Abstract: <p class="Abstract">Current research analyzes the chemical composition of <em>Ligustrum lucidum</em> flower essential oil obtained by the hydrodistillation, and examines its anti-microbial mode of action against food-borne pathogenic bacteria. Gas chromatography-mass spectrometry analysis of the oil resulted in the determination of 44 different compounds, representing 85.2% of the total oil. The oil (1 mg/disc) showed significant antibacterial effect as diameters of inhibition zones (14.6 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…In Table 2 it is presented the results obtained for the antimicrobial activity against the microorganisms under study. The results obtained in the present study for L. lucidum extracts were similar to those reported by Bajpai et al [28] in L. lucidum oil. However, Bacha et al [29] observed lower antimicrobial activity potential in selected medicinal plants from Ethiopia.…”
Section: Some Previous Studies Have Been Performed With Flavonoids Fromsupporting
confidence: 92%
“…In Table 2 it is presented the results obtained for the antimicrobial activity against the microorganisms under study. The results obtained in the present study for L. lucidum extracts were similar to those reported by Bajpai et al [28] in L. lucidum oil. However, Bacha et al [29] observed lower antimicrobial activity potential in selected medicinal plants from Ethiopia.…”
Section: Some Previous Studies Have Been Performed With Flavonoids Fromsupporting
confidence: 92%
“…Recently, the antibacterial activity of essential oils of Buddleja asiatica, Caesalpinia bonducella, Ginkgo biloba and Ligustrum lucidum are reported (Bajpai et al, 2015;Bajpai et al, 2016;Khan et al, 2015;Shukla et al, 2016). Previous studies showed that multiplication of pathogenic Salmonella spp., Escherichia coli (O157:H7), Listeria monocytogenes, Helicobacter pylori and Mycoplasma pneumoniae were inhibited by essential oils (Burt, 2004).…”
Section: Discussionmentioning
confidence: 99%